The Benefits of Early versus Late Therapeutic Intervention in Fabry Disease - Mónica Furlano; Elisabet Ars; Anna Matamala; Vicens Brossa; Joan Martí; Maria del Prado-Venegas; Jaume Crespi; Esther Roe; Roser Torra (Case Reports in Genetics)
Background. Fabry disease (FD) is an X-linked lysosomal storage disorder caused by pathogenic variants of the GLA gene. Heterozygous female patients may show much more variability in clinical manifestations, ranging from asymptomatic to full-blown disease. Because of this heterogeneous clinical picture in women, the diagnosis of FD has typically been delayed for more than a decade, and the optimal time to initiate treatment remains controversial. Case Presentation. Here, we present two unrelated female patients diagnosed with FD harbouring the same pathogenic GLA variant. We discuss the implications of initiating specific therapy at different stages of the disease, with and without organ involvement (early versus late therapeutic intervention). Conclusions. These clinical cases suggest that initiating specific treatment at an earlier age in women with FD may prevent organ involvement and associated clinical events.